The Exposition of Collective Trauma in Short Movie of Bear Story - Wijaya, Kusuma; Santoso, Liora Samantha Valent; Wirnoto, Yasmine Azzah Adillah; Pasopati, Rommel Utungga; Kartiningsih, Rindrah (EJI (English Journal of Indragiri): Studies in Education, Literature, and Linguistics, 2025)
This research analyzes the exposition of trauma in Gabriel Osorio's 2016 short film Bear Story. The film reflects his historical experience under Augusto Pinochet's dictatorship in Chile and tells the story of an old Bear who creates a mechanical diorama depicting the loss of his family due to the dictatorship's oppression. This research uses a narrative and symbol analysis approach to investigate how collective and individual trauma is manifested through visual, narrative and symbolic elements in the film. Trauma is implied in the protagonist's emotional journey as he faces bitter memories of exile, torture and separation. Cinematic techniques such as the use of a soft color palette, melancholic music, and diorama mechanics as a metaphor for the process of memory and healing emphasize the psychological impact of trauma. The results of this study show that Bear stories are not just a form of artistic expression, but also serve as a medium of healing and historical memory for the victims and the wider community. In conclusion, Bear Story emphasizes film as a communicative tool to think trauma, memory, and resistance to oppression in related sociopolitical contexts.